Pengaruh Model Defoliasi Daun Jagung dan Jumlah Benih terhadap Hasil Jagung dan Kacang Nasi pada Sistem Tumpangsari Salome (Kearifan Lokal Timor) - Syprianus Ceunfin; Maria Ursula Humoen; Sonya M. A. Boyfala; Apriana H. Seran; Adrianus Lelang (Fakultas Pertanian, Universitas Timor, 2018)
Salome, a traditional intercropping system that planting several species of crops in the same hole, was established in Timor Island especially in Timor Tengah Utara district for century. To gain the positive interaction among plants and maximize the yields, however, the competition among plants both in vertical and horizontal directions should be reduced. The objectives of this research are to determine the effect of defoliation models and the number of seeds on the yield of maize and rice bean (Vigna umbellata Thunb), and to study Land Equivalent Ratio (LER) in the intercropping system of salome. All treatments of the pot trial were arranged in a Factorial Randomized Completely Block Design 6 x 4 + monoculture with three replicates. The maize leaf defoliation was the first factor consisted of six levels: without defoliation, 50 % leaves defoliation at the upper stem, 100 % leaves defoliation at the upper stem, defoliation of maize leaves leaving only 100% base to flag leaf, leaf blade defoliation from flag leaves to cob, leaf blade defoliation from stem to the cob. The second factor was the comparison of the maize seed numbers to rice bean. It consisted of 4 levels: one of the maize seed to one bean, one seed of local Timor maize to two beans, two seeds of maize to one bean, two seeds of maize to two beans. The results indicated that the maize leaf blade defoliation, maize leaves defoliation from stem to the cob, and the number of seeds increases the maize yield significantly, however, did not significantly affected the yield of rice bean. The LERs intercropping system on Salome models have a total value > 1.